(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A talent centre is one of the most beneficial ways to arouse an individual’s unknown talents. Talent is an outstanding ability of a person. It cannot be lost to someone. Many people say they have no real talent, but it is concealed. We all have inherent talent, and it is unique to everyone. Talent Center is one of those that can greatly help deliver an individual’s talent. It brings out a student’s talent, and the Talent centre also helps students use their own time. Time Management, self-discipline and self-confidence are what the talent centre teaches a student. As a result, many talent centres in various areas can develop talented individuals in art.